(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Vector-borne diseases are illnesses transmitted by arthropods or invertebrates and caused by different microorganisms in human. These diseases accounts for almost 20% of the diseases and disability suffered globally. More than 50% the global population at present projected to be at risk of diseases transmitted by arthropod or invertebrate vectors. Knowledge on the existing perception and practices on transmission of vector borne diseases among rural community would be beneficial to provide a need-based health care delivery system to them. Objective: To know about the perception and practices regarding vector borne diseases in rural community. Materials and Methods: This observational type of crosssectional study was conducted by non-probability purposive sampling method in 474 respondents of Dhamrai and Saturia Upazila from August 2019 to February 2020. Data were analyzed by using Microsoft office packages and calculator and presented in the form of tabulation and diagrams. Results: Findings of this study showed that 76% respondents were Muslims and 35% respondents were above 50 years old. Among 474 respondents, 88% and 78% stated mosquitos and houseflies as vectors responsible for transmitting various diseases, after that 35% Itch mite, 34% Louse and 42% Sandflies. Respectively 72% and 85% respondents stated Malaria and Dengue is transmitted by arthropod vectors, followed by 54% Chikungunya, 35% Kala azar, 13% Filariasis and 33% Typhoid fever. Though, 64%, 67%, 86% and 22% respondents stated bite of mosquito as mode of transmission of malaria, chikungunya, dengue and filariasis correspondingly. In particular, 95%, 87%, 1% and 17% respondents stated personal protection measures, removal of water collection, fogging and spraying as the control measures for mosquito and other vector associated diseases respectively. However, 91%, 74% and 78% respondents used mosquito net, mosquito coil and screening of windows as their frequently used methods for preventing vector borne diseases. Conclusion: Knowledge about arthropod vectors and vector borne diseases at rural level requires improvement. A fair percent of respondents having satisfactory information regarding the name of arthropod vector and illnesses transmitted by them, their mode of transmission in addition to distinct control measures for the prevention of vector borne diseases. Community oriented health education modules should be adopted by the government to boom the knowledge of the village people concerning name of precise vectors and the sicknesses transmitted by means of them. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 33-38